MORAL TEACHINGS AT HOME AS SEEN IN LOUISA MAY ALCOTT’S LITTLE WOMEN - Huili Li; Rizki Februansyah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
The objective of this research is to see the morals taught in the novel Little Women by American white writer Louisa May Alcott. Through these morals, it also aims to study the roots of these morals as part of social values as well as the society of mid-19th century mirrored in the novel.Since the emphasis is on the cultural study, the research is done in the perspective of American Studies. In this case, historical, sociological and cultural approaches are, inevitably, used besides literary approach. All the data used in this research are written text, library research methodology is applied. Books, journals, and many written materials, including internet-based materials, are treated as secondary data, while the novel itself is considered as the primary one. There are three steps in this library research, namely, collecting data, selecting data, and analyzing data. The other method used in this research is analytical-descriptive method, by which all the data obtained are analyzed and presented descriptively. The research shows that American socio-cultural situation in the mid-19th century is basic environment and driving force for the characters’ love, emotion as well as behavior. Its writer Louisa May Alcott arranges the novel structure and preaches proper morals also in accordance with that. A detailed analysis of the American culture here includes its social reform thinking — transcendentalism, literary traditions, women’s social status in the time, and the religious origins behind these values. These cultural heritages reflected in Little Women point out the room for further research on this topic.